Appealing to Moral Exemplars: Shared Perception of Morality as an Essential Ingredient of Intergroup Reconciliation. Issue 1 (9th January 2020) - Čehajić‐Clancy, Sabina; Bilewicz, Michal
Abstract: A history of intergroup conflict threatens the basic sense of in‐group and out‐group morality. This poses a severe obstacle to reconciliation both on socioemotional (by constraining forgiveness and generating dysfunctional intergroup emotions) and on instrumental (by constraining contact opportunities and effectiveness) levels. We argue and review research on how learning about others' moral behavior can contribute to intergroup reconciliation processes. Acknowledging the central role of morality in individual and group perceptions, we propose a new model of reconciliation grounded in research on moral exemplars. Moral exemplars are examples of individual heroic behavior crossing group borders (out‐group members engage in rescuing in‐group members and in‐group members rescuing out‐group members). We demonstrate how intergroup relations in post conflict societies can be improved through learning about moral exemplars. Based on studies and interventions performed in multiple postgenocide and postconflict settings, we suggest that learning about moral exemplars effectively regulates intergroup relations by enabling forgiveness and contact after mass atrocities. We delineate specific policy‐relevant recommendations that may be applied by practitioners working in societies that have been affected by historical crimes. Abstract :